USM RESEARCH ENTRIES IN HIGH-IMPACT JOURNALS STAMP THEIR MARK ON THE WORLD STAGE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 20 April 2016 – The ViceChancellor of Universiti Sains Malaysia (USM) Professor Dato' Dr. Omar Osman was delighted with the achievements of two USM academicians in publishing their research outcomes in two highimpact factor journals, namely Lancet Journal and Nature Genetics Journal recently.